Herbosome an approach to deliver Aegle marmelos extract: Formulation, characterization and stability study - Chauhan, Jaydeep; Gupta, Harshita; Pandey, Komal; Shah, Viral; Kamble, Bhagyashree; Kamble, Bhagyashree (Journal of Drug Delivery and Therapeutics, 2019)
Aegle marmelos fruit has tremendous potential to treat the various ailments for instance; diabetes, microbial diseases and many more. Despite, having abundant therapeutic activity poor lipid solubility and gastric instability limits the efficacy of Aegle marmelos extract (AME). With an idea to overcome these hurdles, AME was formulated as Herbosome in this study. The concept of Herbosome is gaining popularity, as it provides a sheet of lipid on the outer part of drug or extract, which helps in the bioavailability enhancement. In the present work, AME was prepared by cold extraction method and percentage yield was found to be 20% w/w. Here, Marmelosin one of the major phytoconstituent in Aegle marmelos, was used as a marker for standardization of the prepared extract. Further, preliminary phytochemical screening and thin layer chromatography (TLC) was carried out. Whereas, quantitative estimation of Marmelosin in AME by High-performance thin layer chromatography (HPTLC) was conducted. In further steps, pre-formulation parameters (effect of several processes and formulation parameters) were studied and Herbosome loaded AME was formulated by conventional technique i.e. thin film method and soyalecithin were used as phospholipids. Several parameters including, percent entrant efficiency (%EE), particle size, polydispersity index (PDI) and zeta-potential were taken into consideration for the evaluation of AME Herbosome. Later on, followed by, In vitro release of optimized formulation was studied and the formulation was able to release up to 92% even after 12 hours. After developing successful AME Herbosome, stability study was performed as per the International Conference on Harmonisation (ICH) guidelines up to the period of a month. Herbosome was found to be stable at room temperature, even between 2-4ºC. Henceforth, to confirm the efficacy of optimized formulation, In vitro studies (antidiabetic) are going on in the laboratory. Keywords: Aegle marmelos, Aegle marmelos extract, Herbosome, In vitro release, Marmelosin, Thin film method, soyalecithin, and stability study